Spectroscopic and catalytic characterization of Co-exchanged mordenites subject to CO/O2 redox treatments - Gutierrez, Laura Beatriz (2008)
Co-mordenites were prepared by ion exchange and wet impregnation over Na-mordenite and H-mordenite. The prepared solids were calcined and aliquots of these samples were subject to redox treatments first with CO for 2 h at 773 K and then kept 2 h at the same temperature in flowing O2. A thorough characterization of the solids was carried out by TPR, XPS, CO volumetric adsorption, and FTIR with CO, NO and pyridine adsorption as probe molecules. After the redox treatment, Na based samples showed an important increase in the CO adsorption. TPR and XPS results indicated reduction of the oxides present in the calcined samples and the migration of exchanged cobalt from hidden to more exposed sites was demonstrated by FTIR. The acid catalysts did not change their CO capacity of adsorption; exchanged cobalt ions were mainly in β-type sites and remained in this position after treatment. After the redox treatments, the activity for the selective reduction of NOx with methane suffered a decrease on both types of mordenites, probably caused by the strong adsorption of NO and the reduction of β-type Co2+ to metallic cobalt that would diminish the active sites concentration and also block the channels, thus preventing the access of the reactants.